Mango “Ataulfo” peel extract improves metabolic dysregulation in prediabetic Wistar rats - Abraham, Wall-Medrano (2022)
The hypoglycemic effect of functional phytochemicals has been evaluated in diabetic rodents but scarcely in its premorbid condition (prediabetes; PD). This study aimed to evaluate a mango (cv. Ataulfo) peel hydroethanolic (20:80) extract (MPE) for in vivo glycemic/lipidemic-normalizing effect and in vitro enzyme inhibitory ( -amylase/ -glucosidase) activity. The polyphenolic MPE (138 mg EAG.g 1, mainly gallic acid and mangiferin) with antioxidant capacity (DPPH 34 mgTE g 1) was fed to PD rats (induction: high-fat diet (60% energy) + single dose streptozotocin (35 mg kg 1), 4 weeks). At the 8th week, fasting glycemia (FG), oral glucose tolerance test, and insulin sensitivity indexes (HOMA-IR, HOMA- ) > blood lipid-normalizing effect were documented as healthy controls > MPE > disease (PD) controls, which was possibly related to the extract’s concentration–response in vitro enzyme inhibitory activity (IC50 0.085 mg mL 1). MPE is a rich source of glucose-lowering phytochemicals for the primary prevention of type 2 diabetes.